KADROVI I KADROVSKA PITANJA U IZ U BIH / ALLAHSELAMET! - Omerdić, Muharem; Latić, Džemaludin (Novi Muallim, 2009)
KADROVI I KADROVSKA PITANJA U IZ U BIH, Muharem Omerdić ALLAHSELAMET!, Džemaludin Latić